Tensile Strength of S45C Steel Material for SMAW Welding with Various Cooling Media - Sebayang, Alexander; Tarigan, Efrata; Tarigan, Liwat; Ginting, Berta; Irianto, Achmad (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
One of the welding methods that is widely used is the SMAW welding process (Shield Metal Arc Welding) which is also called Electric Arc Welding. This research aims to analyze the effect of variations in cooling media on tensile test results on welding results of S45C steel material. This research uses S45C material. The material is subjected to single vee joint welding, where at the completion of welding the material is immersed in a cooling medium of oil, water, air and is not treated in this research. From the research results, it can be concluded that the highest ultimate tensile strength (Tu) value is when the material is cooled with oil media, where the highest value is 517.15 N/mm2, followed by air cooling media, where the highest value is amounted to 475.85 N/mm2, and the lowest was with water cooling media where the highest value was 455.50 N/mm2. Thus, cooling with oil as a medium is the best between the two cooling media, water and air.